Authentic leadership: application to women leaders - Hopkins, Margaret M.; O’Neil, Deborah A. (Frontiers in Psychology, 2015)
This article provides an overview and critique of authentic leadership, with particular arguments given to support the premise that authentic leadership is a gendered representation of leadership.